Determinants of Whistleblowing Within Local Government’s Internal Auditors - Ujang Hamdani (LPPM Universitas Terbuka, 2022)
The effectiveness of whistleblowing as a part of organization’s internal control depends on the employee’s willingness to become whistleblowers. This research was conducted to examined effect of several individuals and contextual factors of local government’s internal auditors on the whistleblowing intention. Using the theory of planned behavior (TPB), the individual factors in this research were attitudes towards whistleblowing, subjective norms, and perceived whistleblowing control. The prosocial behavior theory was used to explain contextual factors such as independence commitment and public service motivation. Using stratified random sampling, we obtained 201 questionnaires from the population of the local government’s internal auditors in West Kalimantan Province. We used PLS-SEM with higher-order constructs to explain the relationship between components in the model. The research found that only three factors affected whistleblowing intentions: attitudes towards whistleblowing, subjective norms, and perceived whistleblowing control. The conclusion of this research indicates the importance of building an organizational ethical culture, designing definite reporting mechanisms, ensuring the trust of report follow-ups, and guaranteeing protection for whistleblowers.